1997
DOI: 10.1190/1.1444115
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic smoothing in crosswell traveltime tomography

Abstract: Variable-size (dynamic) smoothing operator constraints are applied in crosswell traveltime tomography to reconstruct both the smooth-and fine-scale details of the tomogram. In mixed and underdetermined problems a large number of iterations may be necessary to introduce the slowly varying slowness features into the tomogram. To speed up convergence, the dynamic smoothing operator applies adaptive regularization to the traveltime prediction error function with the help of the model covariance matrix. By so doing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 10 publications
1
49
0
1
Order By: Relevance
“…Th e picked fi rst arrival traveltimes for both the fi ltered and supervirtual traces are inverted by the tomographic procedure described in Nemeth et al (1997); the resulting tomograms are shown in Figure 5a and 5b. Because the actual velocity model is not known, it is not possible to say with certainty which result is correct, but the tomogram from the supervirtual data appear to show much improved resolution of the soil-bedrock interface near the left side of the image and does not contain the low-velocity zone which appears in the raw data tomogram.…”
Section: N T E R F E R O M E T R Y a P P L I C A T I O N Smentioning
confidence: 99%
“…Th e picked fi rst arrival traveltimes for both the fi ltered and supervirtual traces are inverted by the tomographic procedure described in Nemeth et al (1997); the resulting tomograms are shown in Figure 5a and 5b. Because the actual velocity model is not known, it is not possible to say with certainty which result is correct, but the tomogram from the supervirtual data appear to show much improved resolution of the soil-bedrock interface near the left side of the image and does not contain the low-velocity zone which appears in the raw data tomogram.…”
Section: N T E R F E R O M E T R Y a P P L I C A T I O N Smentioning
confidence: 99%
“…The majority of effort, as measured by the topics of published and presented work, has concentrated on developing and improving algorithms for estimating the geophysical parameters themselves (Newman, 1995;Lazaratos et al, 1995;Wilt et al, 1995;Nemeth et al, 1997;Goudswaard et al 1998 to list but a few). In most applications where nongeophysical parameters, such as temperature during a steam flood (Lee et al, 1995) or CO 2 saturations during CO 2 flood Wang et al, 1998) are the object of the crosswell survey, correlations between the geophysical parameters, e.g., velocity or electrical conductivity, and the desired reservoir parameter are derived and used to infer the distribution of reservoir parameters from the distribution of the geophysical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The first arrival travel times of the recorded data were picked and then inverted to find the subsurface velocity model shown in Figure 13 [25,26]. The travel time tomogram represents the variation in seismic wave propagation in both the horizontal and vertical directions.…”
Section: Geophysical Profilesmentioning
confidence: 99%